Epidemiological Factors Associated with Hypertension Among Tribal Population in Gujarat - Bhadresh Mandani; Bhavesh Vaghani; Manishkumar Gorasiya; Parul Patel (Medsci Publications, 2011)
Cardiovascular diseases are recognized as major public health problems by WHO. Very few studies have been carried out among tribal population in India. A cross sectional study was carried out in 2005 to find out the magnitude of hypertension among 154 tribal adults of South Gujarat. WHO classification of hypertension was taken as operational criteria and data was collected in pre-designed, pretested schedule. Blood pressure measurement was done twice on each subject using mercury sphygmomanometer. Overall magnitude of hypertension was found to be 16.9%, and only smoking was found to have significantly associated with it.